Adaptation Strategies of Small-Scale Farmers to Challenges of COVID-19 Pandemic in Osun State, Nigeria - Olufemi Bolarin; Damilola Ajiboye; Sola Komolafe (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The deadly virus COVID-19 has affected not only the health of people but also the food value chain sector. The experience of the locked down period to curtail the spread of the virus was unexpected. It is therefore important to understand how small-scale farmers survived the period. This study examined the strategies employed by small-scale farmers in Osun State to adapt to the challenges resulting from COVID-19 lock down. Specifically, the study itemized types of crops grown by small-scale farmers, assessed the forms of challenges they faced during the COVID-19 pandemic, examined the perceived effects of these challenges on small-scale farming activities, and investigated the adaptation strategies employed by small-scale farmers during this time. Six communities in the local government were selected at random and a total of one hundred and twenty farmers from the communities were interviewed. A questionnaire was designed to collect the primary data. The data was analysed using descriptive statistics and the chi-square tools. Results showed that COVID-19 lock down period led to poor health status (mean=2.87), less transport available to convey farm produce (mean=2.70), and high cost with little/no access to farm inputs such as fertilizer, chemicals and seeds/seedlings (mean=2.62). The foremost effects of these challenges on small scale farming activities were poor marketing of agricultural produce (mean=4.52), decrease in farmers’ income (mean=4.51), and labour shortage (mean=4.39). The leading adaptation strategies employed by the farmers were planting of available grains instead of seeds (mean=2.85), reduced food consumption (mean=2.83), and the use of family labour (mean=2.80). The regression analysis showed that education (β=0.151), marital status (β =1.173), non-farm income (β=-6.790), and years of experience (β=-0.032) were significant (at p<0.05) factors influencing the adaptation strategies employed by the farmers. To effectively reduce the adverse effects of unexpected lockdowns on farmers in the future, it is recommended that outlets for necessary agricultural inputs should be made available in all farming communities